THE COMPARISON BETWEEN TRANSLATION PRODUCTS PRODUCED BY HUMAN RANSLATOR AND MACHINE TRANSLATORS - Solin, Syafiq Anshori M. (TABULARASA, 2014)
The purpose of this study is to describe the comparison between translation products produced by human translator and machine translator. Comparing the translation produced by human translation, online machine translator, and offline machine translator is the main concern ofÂ  the research. The preliminary data taken from an Indonesian popular novel Laskar Pelangi written by Andrea Hirata (2005) and translated into The Rainbow Troops by Angie Kilbane (2009) show how the product of the three translators very often are different from one another.The study on comparing the products of the three tanslators involve the issue of translation procedures which are literal, transference, naturalization, cultural equivalent, functional equivalent, descriptive equivalent, synonymy, through translation, shifts, modulation, recognized translation, translation label, compensation, componential analysis, reduction/expansion, paraphrase, couplets, and notes, addition, glosses. The study also involve the functions of language which consists of expressive function, informative function, and vocative function and in addition, the study also deals with equivalent issue. The issue includes cultural equivalent or Adaptation, functional equivalent, and descriptive equivalent. The findings of this research are google does not recognize a certain Indonesian word but Rekso does. Both Google and Rekso are not capable in maintaining the cultural and functional equivalence of certain words and phrases. The utterances translated by machine translation will be not equivalence.